(untitled) (KULT_online, 2011)
This essay collection focuses, mainly from the point of view of literary studies, on (re)constructions of the subject after its alleged death in postmodernity. However, none of the authors is ready to accept that the subject is dead. Instead, they showcase the manifold ways in which contemporary literature and other media stage the subject’s position between being subjected to social structures and individual agency—a dualism the poststructuralists had all too readily solved in favour of structure.